Pre-sleep Protein Supplementation Affects Energy Metabolism and Appetite in Sedentary Healthy Adults - Hao, Yingying; Li, Xingchen; Zhu, Zheng; Cao, Zhen-Bo (Frontiers in Nutrition, 2022)
Abstract Purpose: To assess the acute effect of pre-sleep protein supplementation combined with resistance exercise on energy metabolism (including 24-h total energy expenditure (TEE), sleep energy expenditure (SEE), basal energy expenditure (BEE), glycolipid oxidation, and appetite of sedentary adults. Methods: A total of thirty-one sedentary participants completed this randomized, double-blind, crossover study. Participants completed the following 24-h experimental conditions in random order in the Human Calorimeter chamber: (1) 40-g protein supplementation with dinner before a nighttime resistance exercise, and followed by pre-sleep placebo intake (PRO-PLA); (2) placebo intake with dinner before a nighttime resistance exercise, and followed by pre-sleep 40-g protein supplementation (PLA-PRO); and (3) placebo supplementation both with dinner and pre-sleep combined with a nighttime resistance exercise (PLA). Subjective appetite score before breakfast the next day was evaluated using the visual analog scale. Results: The SEE values were significantly higher by a mean of 21.7 kcals and 33.3 kcal in PRO-PLA (318.3±44.3 kcal) and PLA-PRO (329.9±45.2 kcal), respectively, than in PLA (296.6±46.6 kcal). In addition, the SEE values for PLA-PRO was also significantly higher by 11.6 kcal than that for PRO-PLA. Further, the fullness the next morning was significantly higher by 30.8% in PLA-PRO (43.9±23.5 mm) than in PLA (33.5±26.6 mm). These effects remained after adjustment for 24-h energy intake. Conclusion: Pre-sleep protein supplementation combined with resistance exercise can significantly increase the SEE and fullness in the next morning, indicating a possible strategy to improve sleep energy metabolism in the sedentary population.